2024
DOI: 10.1200/jco.23.02750
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Osteoradionecrosis in Patients With Head and Neck Cancer Treated With Radiation Therapy: ISOO-MASCC-ASCO Guideline

Douglas E. Peterson,
Shlomo A. Koyfman,
Noam Yarom
et al.

Abstract: ASCO Guidelines provide recommendations with comprehensive review and analyses of the relevant literature for each recommendation, following the guideline development process as outlined in the ASCO Guidelines Methodology Manual . ASCO Guidelines follow the ASCO Conflict of Interest Policy for Clinical Practice Guidelines . Clinical Practice Guidelines and other guidance (“Guidance”) provided by ASCO is not a comprehensive or definitive guide to treatment options. It is intended for voluntary use by providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 138 publications
0
0
0
Order By: Relevance
“…The psychosocial impact of this collective burden of illness can be sufficiently severe to result in severe anxiety, depression, societal withdrawal, and even increased risk of suicide in a subset of head and neck cancer survivors. 26 Despite high-quality evidence, implementation of guidelines into practice has languished. A primary barrier is that coverage benefits for these services have not been provided across private dental insurance payers and by Medicare and Medicaid and therefore many oral health services require individuals to pay out of pocket.…”
Section: The Financial Challengementioning
confidence: 99%
See 1 more Smart Citation
“…The psychosocial impact of this collective burden of illness can be sufficiently severe to result in severe anxiety, depression, societal withdrawal, and even increased risk of suicide in a subset of head and neck cancer survivors. 26 Despite high-quality evidence, implementation of guidelines into practice has languished. A primary barrier is that coverage benefits for these services have not been provided across private dental insurance payers and by Medicare and Medicaid and therefore many oral health services require individuals to pay out of pocket.…”
Section: The Financial Challengementioning
confidence: 99%
“…Treatment-related side effects affecting the oral cavity and oral function include xerostomia/salivary hypofunction, mucositis, pain, soft tissue fibrosis, osteonecrosis of the jaw, dysphagia, nutritional deficiencies, dysarthria, trismus, and surveillance for disease recurrence or new primary cancers. 25,26 Individuals with advanced cancer may require extensive surgical jaw reconstruction, oral prosthetics, and/or voice simulation devices. These costly procedures are medically necessary to improve disease treatment tolerability and enable outcomes that assure basic human functions such as speech and swallowing.…”
Section: The Financial Challengementioning
confidence: 99%
“…Most patients reported that their oncologist recommended dental screening at the start of cancer care (67 of 85 [79%]). Patient adherence to that recommendation was high (71 of 85 Less than high school diploma (1) [9] High school diploma or GED (7) [28] Some college (13) [15]…”
Section: Pre-hnc Dental Carementioning
confidence: 99%
“…Associate's degree (12) [10] Bachelor's degree (40) [23] Master's degree (20) [11] PhD or other doctoral degree (5) [3] Prefer not to say Total household income, $ (n = 81) ≤30 000 (9) [20] 30 001-45 000 (9) [11] 45 001-65 000 (19) [13] 65 001-80 000 (14) [10] 80 001-100 000 (12) [10] 100 001-150 000 (19) [16] 150 001-200 000 (9) [9] >200 000 (11) [12]…”
Section: Pre-hnc Dental Carementioning
confidence: 99%
See 1 more Smart Citation